CHARACTERIZATION OF CHILI SAUCE SMOKED TUNA FISH (THANNUS SP.) - Nurlaeli Fattah; Andi Santi; Agussalim Matti (ITScience (Information Technology and Science), 2022)
The purpose of this study was to determine the shelf life of smoked fish chili sauce and the characterization of smoked tuna chili sauce. Proximate analysis data are presented in the form of tables and bar charts. Quantitative data generated from organoleptic testing were processed using Microsoft Excel and SPSS. Organoleptic test data is presented in the form of a bar chart. Quantitative data from the results of the TPC (Total Plate Count) test were processed using Microsoft Excel and presented in graphical form. Data analysis was carried out descriptively. From the process of making smoked tuna chili sauce, the results are obtained; Guava wood which is used in the smoking process as a source of smoke in tuna, affects the texture, aroma and taste, the characteristics of hard guava wood give a longer burning effect so that it affects the water content of smoked tuna, smoked tuna chili sauce from wood sources different influences on the levels of proximate composition in smoked tuna chili sauce.